2013
DOI: 10.4049/jimmunol.1202500
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin XI Regulates Phagocytosis and Cytokine Secretion in Macrophages

Abstract: Synaptotagmins (Syts) are a group of type I membrane proteins that regulate vesicle docking and fusion in processes such as exocytosis and phagocytosis. All Syts possess a single transmembrane domain, and two conserved tandem Ca2+-binding C2 domains. However, Syts IV and XI possess a conserved serine in their C2A domain that precludes these Syts from binding Ca2+ and phospholipids, and from mediating vesicle fusion. Given the importance of vesicular trafficking in macrophages, we investigated the role of Syt X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…We previously characterized Syt XI as a negative regulator of cytokine secretion and of phagosome maturation (26). In this work, we demonstrated that Syt XI is both degraded by the zinc metalloprotease GP63, and excluded from the phagosome by LPG.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…We previously characterized Syt XI as a negative regulator of cytokine secretion and of phagosome maturation (26). In this work, we demonstrated that Syt XI is both degraded by the zinc metalloprotease GP63, and excluded from the phagosome by LPG.…”
Section: Discussionmentioning
confidence: 80%
“…We previously discovered that Syt XI negatively regulates cytokine secretion and modulates phagosome maturation (26). Because Leishmania affects these processes, we postulated that this parasite may alter Syt XI integrity and function.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations